Preparation of high-corrosion-resistance, wear-resistance and tough surface composite film of aluminum alloy hydraulic cylinder and product

Through the design of micro-nano-slow gradient interface of aluminum alloy and electrochemical preparation solution, combined with temperature alternation and sandblasting treatment, a composite film with high wear resistance and strong corrosion resistance is formed, which solves the problem of aluminum alloy hydraulic cylinder under complex working conditions. The problems of corrosion resistance, wear resistance and fatigue performance improvement have achieved strong surface film-based combination, which is suitable for industrial production.

CN119243283APending Publication Date: 2025-01-03卢飞
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411427986.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Aluminum alloy hydraulic cylinders are prone to instantaneous breaking under complex working conditions, and traditional surface treatment methods are difficult to effectively improve their corrosion resistance, wear resistance and fatigue performance.

Method used

Using aluminum alloy micro-nano-slow gradient interface design and electrochemical preparation scheme of metal-inorganic composite film, a composite film with high wear resistance and strong corrosion resistance is formed through temperature alternating positive and negative high-frequency pulse treatment and sand blasting treatment.

Benefits of technology

It significantly improves the wear resistance, corrosion resistance and fatigue resistance of the aluminum alloy hydraulic cylinder surface, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243283A_ABST
    Figure CN119243283A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a high-corrosion-resistance, wear-resistance and tough surface composite film of an aluminum alloy hydraulic cylinder and a product, and belongs to the technical field of surface treatment of aluminum alloy hydraulic cylinders. The aluminum alloy surface micro-nano slow gradient and composite electrochemical treatment method comprises the following steps: taking an aluminum alloy material as a positive electrode, immersing the aluminum alloy material in a multi-hydroxyl weak acid-strong acid electrolyte, and carrying out temperature alternating positive and negative high-frequency pulse treatment to obtain a surface treatment material; and the surface treatment material is soaked in an ammonium molybdate and thiourea mixed solution to be soaked and subjected to heat treatment, and the surface modified aluminum alloy material is obtained. Based on the aluminum alloy micro-nano slow gradient interface design and the electrochemical preparation scheme of the metal-inorganic composite film, strong film-substrate combination of the surface of the aluminum alloy hydraulic cylinder is achieved, and the corrosion resistance, wear resistance and fatigue resistance of the surface of the aluminum alloy hydraulic cylinder are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment of aluminum alloy hydraulic cylinders, and in particular to the preparation and product of a highly corrosion-resistant, wear-resistant and tough surface composite film for an aluminum alloy hydraulic cylinder. Background Art

[0002] Aluminum alloy hydraulic cylinders have the advantages of light cylinder weight, high pressure resistance, not easy to deform and good heat dissipation performance. They are widely used in high-speed running equipment such as aviation, automobiles, ships, etc., especially in some systems with high lightweight requirements. However, the service conditions of hydraulic parts are complex, and aluminum alloy hydraulic cylinder materials are required to have not only excellent wear and corrosion resistance, but also excellent fatigue resistance. For example, in the engineering machinery industry, its use conditions are generally: cycle frequency 20 to 30 times / min, withstand pressure ≥10MPa, aluminum alloy hydraulic cylinders are prone to instantaneous fracture during use, which seriously affects economic benefits. Based on this, it is usually necessary to perform appropriate surface treatment on the key parts of aluminum alloy hydraulic cylinders to enhance working performance, such as chrome plating, spraying, anodizing and sandblasting grinding. However, traditional surface treatment methods are relatively simple in improving the performance of key components of aluminum alloy hydraulic cylinders, and are still relatively lacking in improving their comprehensive performance. How to solve the corrosion and wear resistance problems of aluminum alloy hydraulic cylinders and improve their mechanical properties such as fatigue is an important direction for the development of the aluminum alloy hydraulic cylinder field. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation and product of a highly corrosion-resistant, wear-resistant and tough surface composite film for an aluminum alloy hydraulic cylinder to solve the above-mentioned problems in the background technology. The present invention realizes a strong film-based bonding on the surface of an aluminum alloy hydraulic cylinder based on the aluminum alloy micro-nano slow gradient interface design and the electrochemical preparation scheme of a metal-inorganic composite film, thereby improving its surface corrosion resistance, wear resistance and fatigue resistance.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention is to provide a method for treating the surface of an aluminum alloy with a micro-nano gradient and a composite electrochemical treatment, comprising the following steps:

[0006] The aluminum alloy material is used as the positive electrode, immersed in a polyhydroxy weak acid-strong acid electrolyte, and subjected to temperature alternating positive and negative high-frequency pulse treatment to obtain a surface-treated material;

[0007] The surface treated material is immersed in a mixed solution of ammonium molybdate and thiourea, and subjected to heat treatment to obtain a surface modified aluminum alloy material.

[0008] Conventional oxidation (constant temperature oxidation) reactions are violent, release heat quickly, and are difficult to accurately control. However, the present invention can slow down the oxidation reaction rate by setting an alternating temperature oxidation method, so that the product can be uniformly film-formed. Moreover, through this variable temperature oxidation operation, micropores with larger pore sizes can be formed under higher temperature treatment, and nanopores can be formed under lower temperature treatment, thereby realizing a micro-nano slow gradient interface.

[0009] The present invention adjusts the distribution of microstress through the microscopic interface design, thereby improving the surface wear resistance and high-frequency fatigue performance of the product.

[0010] Preferably, the aluminum alloy material is an aluminum alloy hydraulic cylinder.

[0011] Preferably, before placing the aluminum alloy material in the polyhydroxy weak acid-strong acid electrolyte, the method further comprises sandblasting the surface of the aluminum alloy material; the sand material used in the sandblasting is silicon dioxide with a particle size of 5-100 mesh, and the time is 3-5 minutes.

[0012] Sand blasting is mainly used to remove oxides on the surface of aluminum alloy materials, play a role in physical cleaning, improve the fatigue performance of the product, and reduce microscopic compressive stress.

[0013] Preferably, the polyhydroxy weak acid-strong acid electrolyte contains the following components: 2-5 vol% H2SO4, 20-60 g / L H3PO4, 30-60 g / L C3H7NO2S (cysteine), and 2-8 g / L sodium carboxybenzenesulfonate.

[0014] The invention adds C3H7NO2S in order to carry out complexation with other trace metal elements in the aluminum alloy material in the solution; and adds sodium carboxylbenzenesulfonate in order to adjust the electrochemical reaction rate.

[0015] Preferably, the positive and negative high-frequency pulse parameters of the temperature alternating positive and negative high-frequency pulse treatment are: the forward current density is 1-2A / dm 2 , negative current density is 0.2-1A / dm 2 , the pulse frequency is 1000-2800Hz, the duty cycle is 50-80%, and the time is 60-150min; the temperature alternating parameters of the temperature alternating positive and negative high-frequency pulse treatment are: the temperature alternating range is 10-30℃, and the alternating adjustment is made at a change rate of 5℃ / min.

[0016] Preferably, the parameters of the ammonium molybdate-thiourea mixed solution are: ammonium molybdate concentration 90-150 g / L, thiourea concentration 40-75 g / L, and pH value 8-10.

[0017] Preferably, the immersion time is 3-5 minutes.

[0018] Preferably, the heat treatment is carried out at a temperature of 300-500° C., for a time of 30-40 min, in a protective atmosphere.

[0019] The second technical solution of the present invention is to provide a surface-modified aluminum alloy material prepared according to the above-mentioned treatment method.

[0020] The beneficial technical effects of the present invention are as follows:

[0021] In order to improve the wear resistance, corrosion resistance and fatigue resistance of the aluminum alloy hydraulic cylinder surface in a complex service environment, the present invention provides a micro-nano slow gradient and composite electrochemical treatment method for the aluminum alloy surface, which combines positive and negative high-frequency pulses with alternating temperature oxidation, and performs surface treatment in a polyhydroxy weak acid-strong acid system, thereby obtaining a composite film with high surface wear resistance and strong corrosion resistance, and at the same time improving the fatigue resistance of the aluminum alloy material. The preparation method designed by the present invention is simple and environmentally friendly, and is suitable for industrial large-scale production.

[0022] The present invention realizes strong film-base bonding on the surface of aluminum alloy hydraulic cylinder based on aluminum alloy micro-nano slow gradient interface design and electrochemical preparation scheme of metal-inorganic composite film, thereby improving its surface corrosion resistance, wear resistance and fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of the micro-nano slow gradient structure on the surface of the product of Examples 1-6.

[0025] Figure 2 This is the surface morphology of the surface treated hydraulic cylinder in Example 1.

[0026] Figure 3 Surface morphology of the products of Examples 1 to 6. (a), (b), (c), (d), (e), and (f) are surface morphology of the products of Examples 1, 2, 3, 4, 5, and 6, respectively.

[0027] Figure 4 The load-displacement curves of the products of Examples 1-5 and the surface treated hydraulic cylinder in Example 1.

[0028] Figure 5This is a surface fatigue fracture crack source diagram of the product of Example 1. Among them, (a) is the fatigue source area, (b) is the enlarged diagram of the fatigue source area, (c) is the expansion area, and (d) is the instantaneous fracture area.

[0029] Figure 6 (a) is the microscopic morphology of the surface of the product of comparative example 1 and (b) is the fatigue fracture crack source diagram.

[0030] Figure 7 (a) is the microscopic morphology of the surface of the product of Comparative Example 2 and (b) is the fatigue fracture crack source diagram. DETAILED DESCRIPTION

[0031] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0035] The particle size of the silicon dioxide used in the following examples and comparative examples of the present invention is 80-100 mesh.

[0036] The neutral salt spray test in the present invention is carried out in accordance with the national standard GB / T 10125-2012.

[0037] The material of the aluminum alloy hydraulic cylinder used in the present invention is 6 series aluminum alloy.

[0038] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0039] Example 1

[0040] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0041] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 5vol% H2SO4, 20g / L H3PO4, 30g / L C3H7NO2S, 2g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 2A / dm 2 , negative current density is 1A / dm 2 , the pulse frequency is 1800Hz, the duty cycle is 50%, and the time is 100min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 130g / L, thiourea concentration is 60g / L, and pH value is 8), immersed for 4min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0042] According to statistics, the surface protective film thickness of the product of this embodiment is 52μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.008; the surface nanohardness is 620HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 710,000 times.

[0043] Example 2

[0044] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0045] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 5vol% H2SO4, 60g / L H3PO4, 45g / L C3H7NO2S, 8g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 1A / dm 2 , negative current density is 0.2A / dm 2, the pulse frequency is 1000Hz, the duty cycle is 80%, and the time is 60min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 130g / L, thiourea concentration is 60g / L, and pH value is 8), immersed for 5min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0046] According to statistics, the surface protective film thickness of the product of this embodiment is 48μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.007; the surface nanohardness is 630HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 725,000 times.

[0047] Example 3

[0048] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0049] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 4vol% H2SO4, 50g / L H3PO4, 40g / L C3H7NO2S, 6g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 1.8A / dm 2 , negative current density is 0.2A / dm 2 , the pulse frequency is 1000Hz, the duty cycle is 60%, and the time is 150min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 140g / L, thiourea concentration is 40g / L, and pH value is 9), immersed for 5min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0050] According to statistics, the surface protective film thickness of the product of this embodiment is 58μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.003; the surface nanohardness is 615HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 695,000 times.

[0051] Example 4

[0052] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0053] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 5vol% H2SO4, 30g / L H3PO4, 50g / L C3H7NO2S, 6g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 1.6A / dm 2 , negative current density is 0.4A / dm 2 , the pulse frequency is 2200Hz, the duty cycle is 80%, and the time is 120min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 120g / L, thiourea concentration is 55g / L, and pH value is 9), immersed for 5min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0054] According to statistics, the surface protective film thickness of the product of this embodiment is 47μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.005; the surface nanohardness is 632HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 730,000 times.

[0055] Example 5

[0056] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0057] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 3vol% H2SO4, 50g / L H3PO4, 45g / L C3H7NO2S, 6g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 1.6A / dm 2 , negative current density is 0.4A / dm2 , the pulse frequency is 2200Hz, the duty cycle is 60%, and the time is 90min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 130g / L, thiourea concentration is 40g / L, and pH value is 9), immersed for 5min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0058] According to statistics, the surface protective film thickness of the product of this embodiment is 45μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.005; the surface nanohardness is 611HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 720,000 times.

[0059] Example 6

[0060] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0061] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 4vol% H2SO4, 40g / L H3PO4, 60g / L C3H7NO2S, 8g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and temperature alternating positive and negative high-frequency pulse treatment was performed to obtain a surface-treated hydraulic cylinder; wherein, the parameters of the positive and negative high-frequency pulses are: the forward current density is 2A / dm 2 , negative current density is 0.8A / dm 2 , the pulse frequency is 2800Hz, the duty cycle is 80%, and the time is 130min; the temperature alternation parameters are: the temperature alternation range is 10-30℃, and the alternation adjustment is made at a rate of 5℃ / min. After the surface treatment, the surface treated hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in a mixed solution of ammonium molybdate and thiourea (ammonium molybdate concentration is 150g / L, thiourea concentration is 70g / L, and pH value is 10), immersed for 5min under continuous stirring, and finally heat treated at 300℃ for 30min in a nitrogen atmosphere to obtain a surface modified aluminum alloy hydraulic cylinder.

[0062] According to statistics, the surface protective film thickness of the product of this embodiment is 54μm, there is no corrosion after 1200 hours of neutral salt spray test, and the viscous friction coefficient is 0.004; the surface nanohardness is 601HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 740,000 times.

[0063] Comparative Example 1 (the only difference from Example 6 is that the temperature alternating positive and negative high-frequency pulse treatment and heat treatment are omitted)

[0064] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0065] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was immersed in an ammonium molybdate-thiourea mixed solution (ammonium molybdate concentration of 150g / L, thiourea concentration of 70g / L, pH value of 10) for 5min under continuous stirring to obtain a surface-modified aluminum alloy hydraulic cylinder.

[0066] According to statistics, the surface protective film thickness of the product of this comparative example is 6μm, and the corrosion is serious after 1200 hours of neutral salt spray test (corrosion products begin to be generated after 120 hours), and the viscous friction coefficient is 0.12; the surface nanohardness is 230HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 500,000 times.

[0067] Comparative Example 2

[0068] A surface treatment method for an aluminum alloy hydraulic cylinder, the steps are as follows:

[0069] The surface of the aluminum alloy hydraulic cylinder was sandblasted (time 3min, abrasive type silica, spray gun pressure 3Mpa, nozzle diameter 2mm, sandblasting distance 20cm). The sandblasted hydraulic cylinder was connected to the positive electrode of the power supply through a hanger, and then immersed in an electrolyte (the electrolyte contains the following components: 5vol% H2SO4, 20g / L H3PO4, 30g / L C3H7NO2S, 2g / L sodium carboxylbenzenesulfonate), with a pure aluminum plate as the cathode, and constant temperature electrolytic surface treatment was performed to obtain a surface treated hydraulic cylinder; wherein the parameters of the constant temperature electrolytic surface treatment are: a constant current density of 2A / dm 2 , temperature is 10℃, time is 100min. After the surface treatment, the hydraulic cylinder is taken out, rinsed with pure water for 3 times, immersed in ammonium molybdate thiourea mixed solution (ammonium molybdate concentration is 150g / L, thiourea concentration is 70g / L, pH value is 10), immersed for 5min under continuous stirring to obtain a surface modified aluminum alloy hydraulic cylinder.

[0070] According to statistics, the surface protective film thickness of the product of this comparative example is 46μm, corrosion occurs after 1200 hours in the neutral salt spray test, and the viscous friction coefficient is 0.03; the surface nanohardness is 390HV; a high-frequency fatigue test is carried out at 300Mpa, and the number of fatigue fractures is measured to be 410,000 times.

[0071] Figure 1 Schematic diagram of the micro-nano slow gradient structure on the surface of the product of Examples 1-6.

[0072] Figure 2 This is the surface morphology of the surface treated hydraulic cylinder in Example 1.

[0073] Depend on Figure 2 It can be seen that after the corresponding treatment of the present invention, an ordered structure is formed on the surface of the surface-treated hydraulic cylinder, including micron-scale strands and nanometer-scale holes. This structure can provide good bonding force for subsequent composite treatment.

[0074] Figure 3 Surface morphology of the products of Examples 1 to 6. (a), (b), (c), (d), (e), and (f) are surface morphology of the products of Examples 1, 2, 3, 4, 5, and 6, respectively.

[0075] Depend on Figure 3 It can be seen that the holes on the surface of the material have been filled with composite particles and the surface film is dense.

[0076] Effect verification

[0077] (1) The above samples were subjected to nanoindentation test according to GB / T 22458-2008. The test results are as follows: Figure 4 shown.

[0078] Figure 4 The load-displacement curves of the products of Examples 1-5 and the surface treated hydraulic cylinder in Example 1.

[0079] Figure 4 The "not subjected to composite treatment" refers to the relevant data of the surface treated hydraulic cylinder in Example 1.

[0080] (2) A high-frequency fatigue test was conducted at 300 MPa, and the data was measured at 740,000 cycles. The test results are as follows: Figure 5-7 shown.

[0081] Figure 5 This is a surface fatigue fracture crack source diagram of the product of Example 1. Among them, (a) is the fatigue source area, (b) is the enlarged diagram of the fatigue source area, (c) is the expansion area, and (d) is the instantaneous fracture area.

[0082] Depend on Figure 5 It can be seen that the initiation of crack sources is single-source initiation, no fatigue band is seen in the fatigue extension zone, and obvious dimple morphology is seen in the instantaneous fracture zone. The fracture mechanism is quasi-cleavage fracture.

[0083] Figure 6 (a) is the microscopic morphology of the surface of the product of comparative example 1 and (b) is the fatigue fracture crack source diagram.

[0084] Depend on Figure 6 It can be seen that there are more fatigue fracture crack sources and the expansion area is smaller.

[0085] Figure 7 (a) is the microscopic morphology of the surface of the product of Comparative Example 2 and (b) is the fatigue fracture crack source diagram.

[0086] Depend on Figure 7 It can be seen that the fracture zone is irregular, the number of fatigue fracture crack sources increases, and the expansion zone area is small.

[0087] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for treating aluminum alloy surface with micro-nano gradient and composite electrochemical treatment, characterized in that: The following steps are involved: The aluminum alloy material is used as the positive electrode, immersed in a polyhydroxy weak acid-strong acid electrolyte, and subjected to temperature alternating positive and negative high-frequency pulse treatment to obtain a surface-treated material; The surface treated material is immersed in a mixed solution of ammonium molybdate and thiourea, and subjected to heat treatment to obtain a surface modified aluminum alloy material.

2. The processing method according to claim 1, characterized in that: The polyhydric hydroxy weak acid-strong acid electrolyte contains the following components: 2-5 vol% H2SO4, 20-60 g / L H3PO4, 30-60 g / L C3H7NO2S, and 2-8 g / L sodium carboxybenzenesulfonate.

3. The processing method according to claim 1, characterized in that: The positive and negative high-frequency pulse parameters of the temperature alternating positive and negative high-frequency pulse treatment are: the forward current density is 1-2A / dm 2 , negative current density is 0.2-1A / dm 2 , the pulse frequency is 1000-2800Hz, the duty cycle is 50-80%, and the time is 60-150min; the temperature alternating parameters of the temperature alternating positive and negative high-frequency pulse treatment are: the temperature alternating range is 10-30℃, and the alternating adjustment is made at a change rate of 5℃ / min.

4. The processing method according to claim 1, characterized in that: The parameters of the ammonium molybdate-thiourea mixed solution are: ammonium molybdate concentration 90-150 g / L, thiourea concentration 40-75 g / L, and pH value 8-10.

5. The processing method according to claim 1, characterized in that: The immersion time is 3-5 minutes.

6. The processing method according to claim 1, characterized in that: The heat treatment temperature is 300-500° C., the time is 30-40 min, and the atmosphere is a protective atmosphere.

7. A surface-modified aluminum alloy material prepared according to the treatment method according to any one of claims 1 to 6.